The Influence of Competence, Individual Behavior, and Blended Learning on Training Participants' Satisfaction - Sarjayadi, Sarjayadi; Putri, Nora Eka; Magriasti, Lince; Frinaldi, Aldri (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This study aims to analyze the influence of competence, individual behavior, and blended learning on the satisfaction of participants in leadership training at the Regional Human Resource Development Center in Bukittinggi, both partially and simultaneously. The population of this study consists of all participants of the Administrator Leadership Training (PKA) in 2023 at the PPSDM Regional Bukittinggi, totaling 241 participants. The sampling technique used in this study is proportional random sampling, with a sample size of 151 respondents. Data in this study were collected using a survey method with a questionnaire. The data analysis used in this study is descriptive and quantitative analysis, where hypothesis testing was conducted using multiple linear regression. Based on the results, the study found that: 1) Competence has a positive and significant partial effect on the satisfaction of Administrator Leadership Training participants, with the t-value (6.015) greater than the t-table value (1.655), and the significance of 0.000 is less than 0.05; 2) Individual behavior also has a positive and significant partial effect on participant satisfaction, with the t-value (2.781) greater than the t-table value (1.655), and the significance of 0.007 is less than 0.05; 3) Blended learning also has a positive and significant partial effect on the satisfaction of Administrator Leadership Training participants, with the t-value (2.759) greater than the t-table value (1.655), and the significance of 0.007 is less than 0.05. Furthermore, simultaneously, competence, individual behavior, and blended learning also have a positive and significant effect on the satisfaction of leadership training participants at the PPSDM Regional Bukittinggi.